2008
DOI: 10.1016/j.healun.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The Real Estate of Myoblast Cardiac Transplantation: Negative Remodeling Is Associated With Location

Abstract: Background-Skeletal myoblast (SKMB) transplantation has been proposed as a therapy for ischemic cardiomyopathy due to its possible role in myogenesis. The relative safety and efficacy based on location within scar is not known. We hypothesized that SKMB transplanted into peripheral scar (compared to central scar) would more effectively attenuate negative left ventricular (LV) remodeling but at the risk of arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…Extensive and indepth experimental efforts from various research groups have assessed the performance of skeletal myoblasts for the treatment of both ischemic and nonischemic cardiomyopathies both in small mouse [32], rat [28,45], rabbit [46,47], large sheep [40,48], dog [49,50] and pig [22,5153] models. These studies have demonstrated that skeletal myoblasts effectively prevented left ventricular remodeling and preserved global parameters (ejection fraction and left ventricular pressure) as well as regional parameters (regional stroke work at the infarct site, wall thickness and myocardial tissue velocities) of myocardial contractility.…”
Section: Experimental Animal Studies Using Skeletal Myoblasts For Myomentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive and indepth experimental efforts from various research groups have assessed the performance of skeletal myoblasts for the treatment of both ischemic and nonischemic cardiomyopathies both in small mouse [32], rat [28,45], rabbit [46,47], large sheep [40,48], dog [49,50] and pig [22,5153] models. These studies have demonstrated that skeletal myoblasts effectively prevented left ventricular remodeling and preserved global parameters (ejection fraction and left ventricular pressure) as well as regional parameters (regional stroke work at the infarct site, wall thickness and myocardial tissue velocities) of myocardial contractility.…”
Section: Experimental Animal Studies Using Skeletal Myoblasts For Myomentioning
confidence: 99%
“…These studies have demonstrated that skeletal myoblasts effectively prevented left ventricular remodeling and preserved global parameters (ejection fraction and left ventricular pressure) as well as regional parameters (regional stroke work at the infarct site, wall thickness and myocardial tissue velocities) of myocardial contractility. The diastolic properties also demonstrated improvement with increased compliance of the infarcted myocardium [47,54]. …”
Section: Experimental Animal Studies Using Skeletal Myoblasts For Myomentioning
confidence: 99%
“…85 In a rabbit MI model, injection of SkM in the infarct border zone led to erratic ventricular ectopy, 86 and injection of SkMs in the scar center elicited negative LV remodeling and late ventricular ectopies. 87 Intramyocardial injection of bone marrow mononuclear cells (BMMNCs) in a rat chronic heart failure model 88 also generated cell clusters in the infarct border zone, which most likely were responsible for the increased ventricular arrhythmias. Myocardial injection per se may also lead to scarring.…”
Section: Future Electrophysiological Challenges In Cardiomyogenesismentioning
confidence: 99%
“…For this reason, it is important to deliver the maximum available cells. The technical approach used to implant the cells could influence the efficacy of cellular CMP [33,34]. In fact, cell mortality after transplantation appears to be more important when grafted in the center of highly fibrotic ischemic scars (decreased oxygen and nutrient supply to the chronic ischemic myocardium).…”
Section: Cell Deliverymentioning
confidence: 99%